Living Qur’an: Rutinitas Sholat Tasbih (Sewelasan) (Studi Kasus di Pondok Pesantren Darun Najah Desa Sambikarto Kecamatan Sekampung Kabupaten Lampung Timur) - Hidayah, Nikmatul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2021)
Abstract: Research on bringing the Qur'an to life in the middle of Islamic boarding school life. The series of activities consisted of sunnah hajat prayers, sunah tasbih prayers, tahlil, istighosah and management of Sheikh Abdul Qadir al-Jailani. The object of research at Darun Najah Islamic Boarding School used a phenomenological approach with interview and observation methods. Research proves the existence of a transmission process, namely the connection between sanad and Pondok Pesantren Darussalam Way Jepara. The practice has not undergone a transformation because both in Pondok Pesantren Darussalam or Pondok Pesantren Darun Najah the practice of praying is a mandatory activity, if it does not follow without any definite reason then it gets the consequences. The process of forming activities through three stages: 1) externalization: the activity is made compulsory by caregivers and administrators, 2) objectification: students become accustomed to it and feel light and 3) internalization: many santris feel the pleasure of doing worship.